2017
DOI: 10.1242/dmm.028738
|View full text |Cite
|
Sign up to set email alerts
|

The role of Ca2+ signaling in Parkinson's disease

Abstract: Across all kingdoms in the tree of life, calcium (Ca2+) is an essential element used by cells to respond and adapt to constantly changing environments. In multicellular organisms, it plays fundamental roles during fertilization, development and adulthood. The inability of cells to regulate Ca2+ can lead to pathological conditions that ultimately culminate in cell death. One such pathological condition is manifested in Parkinson's disease, the second most common neurological disorder in humans, which is charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(106 citation statements)
references
References 320 publications
(321 reference statements)
1
105
0
Order By: Relevance
“…Calcium ions can trigger AS aggregation in vitro , even at low micromolar concentrations, and thus, it has been proposed that Ca(II) might induce cytoplasmic AS aggregates in cells (Nath et al ; Follett et al ; Rcom‐H’cheo‐Gauthier et al ). Accordingly, the study of AS‐Ca(II) interactions and their role in protein aggregation and Parkinson’s disease became an active area of research in the last years (Rcom‐H’cheo‐Gauthier et al ; Zaichick et al ). Here we summarized the most important recent findings.…”
Section: α‐Synuclein Is a Metal‐binding Proteinmentioning
confidence: 99%
“…Calcium ions can trigger AS aggregation in vitro , even at low micromolar concentrations, and thus, it has been proposed that Ca(II) might induce cytoplasmic AS aggregates in cells (Nath et al ; Follett et al ; Rcom‐H’cheo‐Gauthier et al ). Accordingly, the study of AS‐Ca(II) interactions and their role in protein aggregation and Parkinson’s disease became an active area of research in the last years (Rcom‐H’cheo‐Gauthier et al ; Zaichick et al ). Here we summarized the most important recent findings.…”
Section: α‐Synuclein Is a Metal‐binding Proteinmentioning
confidence: 99%
“…The top-ranked GO terms are associated with GPCR signaling, calcium homeostasis, and sensory perception 17/30 (Table S6). The calcium ion homeostasis dysregulation is an important pathological feature of PD [2] and is associated with α-syn aggregation and neuronal death [102].…”
Section: Age-dependent Pathway/go Changesmentioning
confidence: 99%
“…It was reported that the expression of CBPs in general is very low in case of SNc neurons (Chung et al, 2005;Greene et al, 2005;Mendez et al, 2005) and reduces even further under PD (Fairless et al, 2019;Hurley et al, 2013;Yamada et al, 1990;Zaichick et al, 2017).…”
Section: Enhancement Of Cbp Expressionmentioning
confidence: 99%
“…In the proposed model, intracellular calcium concentration in the SNc neuron is dependent on calcium-binding proteins, mitochondria (MT) and endoplasmic reticulum (ER) (Zaichick et al, 2017;Zündorf and Reiser, 2011). The intracellular calcium concentration dynamics ([ ]) of the SNc neuron (Muddapu and Chakravarthy, 2020) is given by,…”
Section: Biophysical (Conductance-based) Neuron Model (Snc)mentioning
confidence: 99%